Jóhanna Jónsdóttir: Europeanization and the European Economic Area: Iceland’s Participation in the EU’s Policy Process - Conrad, Maximilian (Stjórnsýslustofnun, 2013)
Extraction: Drawing on unique material, the book presents an empirically rich and theoretically relevant contribution not just to issues regarding the role of small states within or outside the union, but also allows for broader conclusions regarding the institutional logics that explain political action in the context of European integration. In the Icelandic context, its relevance stems mainly from the fact that it asks a somewhat different question: it is not interested in the potential role that Iceland may have as a full member of the EU, but instead analyzes the channels for influence that are available already today to non-members such as the three EEA/EFTA countries Iceland, Norway and Liechtenstein.